2020
DOI: 10.1002/biof.1670
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microRNA‐27b‐3p relieves osteoarthritis pain via regulation of KDM4B‐dependent DLX5

Abstract: Osteoarthritis (OA) represents a progressive degenerative disorder that predominantly affects the synovial membranes of joints. Recent studies have highlighted the significant role played by microRNAs (miRNAs) in OA development. The current study aimed to elucidate the underlying modulatory role of miR-27b-3p in the development of OA. The expression of miR-27b-3p in the OA patients and rat models post anterior cruciate ligament transection operation was measured using reverse transcription quantitative polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…On the other hand, miR-27b-3p was reported to be highly expressed in both samples collected from OA patients and rat models. Suppression of miR-27b-3p promotes the expression of the osteogenic differentiation markers while inhibiting the expression of the adipogenic differentiation markers, inflammatory factors, cellular senescence of bone marrow mesenchymal stem cells (BMSCs), and alleviating OA pain in rats by demethylation of KDM4B (Lysine demethylase 4B) 78 . These observations may explain our previous finding that the lameness score in donkeys has decreased with the progression of OA 1 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, miR-27b-3p was reported to be highly expressed in both samples collected from OA patients and rat models. Suppression of miR-27b-3p promotes the expression of the osteogenic differentiation markers while inhibiting the expression of the adipogenic differentiation markers, inflammatory factors, cellular senescence of bone marrow mesenchymal stem cells (BMSCs), and alleviating OA pain in rats by demethylation of KDM4B (Lysine demethylase 4B) 78 . These observations may explain our previous finding that the lameness score in donkeys has decreased with the progression of OA 1 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, miR27b-3p was reported to be highly expressed in both samples collected from OA patients and rat models. Suppression of miR-27b-3p promotes the expression of the osteogenic differentiation markers while inhibiting expression of the adipogenic differentiation markers, in ammatory factors, cellular senescence of bone marrow mesenchymal stem cells (BMSCs), and alleviating OA pain in rats by demethylation of KDM4B (Lysine demethylase 4B) [79]. These observations may explain our previous nding that lameness score in donkeys has been decreased with the progression of OA [1] Concerning COL10A1 expression level in the current study, it increased in the 2 nd , and 3 rd months with the highest level at the 1 st month after MIA injection, then downregulated at 5 th and 7 th months.…”
Section: Discussionmentioning
confidence: 99%
“…CeRNA XIST/miR-211/CXCR4 have been reported to promote the proliferation of OA chondrocytes and promote apoptosis [ 7 ]. Many studies have confirmed that miRNAs participate in the differentiation regulation of bone marrow mesenchymal stem cells (BMSCs) [ [8] , [9] , [10] ]. One of our previous studies revealed that miR-132-3p, miR-99a, miR-127-5p, and miR-125b-3p play essential roles in the tending induction of rat BMSCs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%